2021
DOI: 10.1038/s41598-021-00509-x
|View full text |Cite
|
Sign up to set email alerts
|

FAN score comprising fibrosis-4 index, albumin–bilirubin score and neutrophil–lymphocyte ratio is a prognostic marker of urothelial carcinoma patients treated with pembrolizumab

Abstract: It is important to identify prognostic and predictive markers of metastatic urothelial carcinoma (mUC) treated with immunocheckpoint inhibitors. We sought to establish a prognostic marker for patients with mUC treated with pembrolizumab based on only blood test results. We included 165 patients with mUC in the discovery cohort and 103 with mUC who were treated with pembrolizumab in the validation cohort. Multivariate and Cox regression analyses were used to analyse the data. In the discovery cohort, the fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 34 publications
(46 reference statements)
0
23
0
Order By: Relevance
“…Several studies have demonstrated that ALB regulates inflammatory responses by binding to lipopolysaccharides and reactive oxygen species [ 28 ]. Moreover, data have been accumulating on the utility of albumin as a prognostic marker, including the prognostic value of different albumin parameters alone or when combined [ 29 , 30 ]. ALP catalyzes the hydrolysis of phosphate esters and is responsible for transferring phosphate groups, which are mainly produced in the liver and bone.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that ALB regulates inflammatory responses by binding to lipopolysaccharides and reactive oxygen species [ 28 ]. Moreover, data have been accumulating on the utility of albumin as a prognostic marker, including the prognostic value of different albumin parameters alone or when combined [ 29 , 30 ]. ALP catalyzes the hydrolysis of phosphate esters and is responsible for transferring phosphate groups, which are mainly produced in the liver and bone.…”
Section: Discussionmentioning
confidence: 99%
“…Sex, age at metastasis, primary cancer site, presence of local treatment, presence of liver metastasis, the regimen of induction chemotherapy, number of induction chemotherapy cycles, the efficacy of induction chemotherapy, the Eastern Cooperative Oncology Group‐Performance Status (ECOG‐PS) score, presence of treatment with pembrolizumab after first‐line chemotherapy, serum creatinine clearance, and the serum Fib‐4 index, ALBI, and neutrophil‐to‐lymphocyte ratio (FAN) score 15 were analyzed. Local treatment included radical cystectomy, nephroureterectomy, and radiation therapy, but not transurethral resection for bladder cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were also collected at discharge, and the FIB-4 index, ALBI score and NLR were calculated using the following formulae: FIB-4 index = age (years) × aspartate transaminase (U/L) / (platelet count [10 9 /L] × alanine aminotransferase [U/L] 1/2 ) 16) ALBI score = (log10 total bilirubin [mmol/L] × 0.66) + (albumin [g/L] × -0.085) 17) NLR = neutrophil count/lymphocyte count The original FAN score was calculated using the following cut-off values: Fib-4 index > 3.5, ALBI score > -2.6, and NLR > 5.0, assigning one point for each index (minimum score 0, maximum score 3). 12) In the current study, we not only calculated the FAN score based on these criteria, but also calculated this score using different cut-off values, determined by the median values in our heart failure cohort (HF-FAN score), similarly assigning one point for each index criteria that was met (minimum score 0, maximum score 3).…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Recently, the FAN score, comprising the FIB-4 index, ALBI score and NLR, was developed as a useful risk stratification tool in patients with urothelial carcinoma. 12) This simple score might also be promising for heart failure since inflammation and the deterioration of liver function are associated with the development of heart failure. 13,14) However, the cut-off values of these 3 components were determined based on data from a non-heart failure population.…”
mentioning
confidence: 99%
See 1 more Smart Citation